Experimental and computational analysis of magnetization reversal in (Nd, Dy)-Fe-B core shell sintered magnets. (1st April 2017) - Helbig, Tim; Loewe, Konrad; Sawatzki, Simon; Yi, Min; Xu, Bai-Xiang; Gutfleisch, Oliver
Abstract: (Nd, Dy)-Fe-B core shell model magnets were prepared by co-sintering Nd-Fe-B and (Nd, Dy)-Fe-B powders. The Nd-Fe-B core and partially Dy substituted i.e. (Nd, Dy)-Fe-B shell were identified by SEM. MFM measurements of the remanent state revealed a magnetic contrast of core and shell within the same grain. The magnetization reversal of a representative core-shell grain was investigated by in-situ MFM and magneto-optical Kerr microscopy at room temperature in varying magnetic fields. Micromagnetic simulation was carried out in addition to resolve the specific nucleation site for the reversal. It was found that the position of the nucleation site depends critically on the magnetocrystalline anisotropy K edge in the shell edge which is defined as the defect layer in the shell surface. Low and high K edge favors the nucleation in the shell and core, respectively. Once the nucleation occurs in the core, the nucleation field or coercivity does not rely on K edge . Graphical abstract: Image 1